1988
DOI: 10.1123/ijsb.4.1.38
|View full text |Cite
|
Sign up to set email alerts
|

The Marathon Skate in Nordic Skiing Performed on Roller Skates, Roller Skis, and Snow Skis

Abstract: In the past few years there has been a change from emphasizing the classical cross-country ski technique to introducing the skating technique. Use of the skating stride has led to the adoption of roller skates instead of the ratchet-type roller skis for dryland training. Therefore the question arises as to whether the roller skates simulate the movement pattern observed on snow. This study attempted to answer this question and to evaluate the movement similarity between a newly designed skating-specific roller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For these reasons, in-line skates have been criticized as not satisfactorily allowing for the simulation of Downloaded by [Oregon State University] at 17:11 04 January 2015 cross-country skiing. In comparing the kinematics of in-line skating and roller skiing with on-snow skiing, Gervais and Wronko (1988) found that both dry-land devices approximated the pattern of the marathon skate technique on snow, but that discrepancies in the propulsive phase suggested that the roller skis more closely simulated the on-snow technique. One group compared the physiological responses induced by the doublepole and VI skate techniques with in-line skates, roller skis and snow skis.…”
Section: Training Implicationsmentioning
confidence: 93%
See 2 more Smart Citations
“…For these reasons, in-line skates have been criticized as not satisfactorily allowing for the simulation of Downloaded by [Oregon State University] at 17:11 04 January 2015 cross-country skiing. In comparing the kinematics of in-line skating and roller skiing with on-snow skiing, Gervais and Wronko (1988) found that both dry-land devices approximated the pattern of the marathon skate technique on snow, but that discrepancies in the propulsive phase suggested that the roller skis more closely simulated the on-snow technique. One group compared the physiological responses induced by the doublepole and VI skate techniques with in-line skates, roller skis and snow skis.…”
Section: Training Implicationsmentioning
confidence: 93%
“…In addition, the common dry-land training technique of running with poles does not simulate skating nearly as well as it simulates the diagonal stride technique. However, as pointed out by several investigators, some caution must be applied to obtain optimal specificity from roller skiing (Baumann, 1985;Dillman and Dufek, 1983;Gervais and Wronko, 1988;Pinchak et al, 1987b;Yudin and Fedotov, 1975). Roller skis are typically at least one and a half times the weight of on-snow racing skis (Street, 1988), and obviously have a different interface with the skiing surface.…”
Section: Training Implicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…In other words, a given increase in body mass should theoretically result in a proportionally smaller increase in the mechanical power cost. Although there are biomechanical differences between roller skiing and snow skiing (Dillman & Dufek, 1983;Gervais & Wronko, 1988;Pinchak, Hancock, Hagen, & Hall, 1987;Yudin & Fedotov, 1975), the theoretical relationships of P,, P, , P, , and Pa with body mass should not differ between these two activities. However, there does appear to be an important difference for P,.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Additionally, searching with "marathon" and "skate" in the title field gave one relevant hit, i.e. Gervais and Wronko [8].…”
Section: Introductionmentioning
confidence: 99%